Electrocatalytic Properties of Immobilized Heme Proteins: Basic Principles and Applications. Issue 20 (26th September 2019) - Ranieri, Antonio; Bortolotti, Carlo Augusto; Di Rocco, Giulia; Battistuzzi, Gianantonio; Sola, Marco; Borsari, Marco
Abstract: Heme proteins encompass redox enzymes, electron transferases, and species for dioxygen transport and storage. Upon immobilization on a conductive surface, heme proteins can accomplish bioelectrocatalysis. In this process, they carry out oxidation or reduction of substrates at a solid electrode acting as electron acceptor or donor, respectively, thanks to electron transfer processes occurring at the interphase. The efficiency of bioelectrocatalysis depends on the electrical communication of the protein with the electrode surface, retention of protein structure upon adsorption and accessibility of the substrate to the active site. This Minireview outlines the main factors affecting bioelectrocatalysis by adsorbed heme proteins, highlights open issues, and summarizes recent advances in the field. Abstract : Heme works better inside a protein : Heme proteins improve performance and selectivity of the heme catalytic activity. An overview of the advances in the exploitation of this class of proteins in bioelectrocatalytic processes in the fields of human health, environment and chemical synthesis is offered, along with an outline of upcoming opportunities and perspectives.